The Image of a Schoolgirl in Popular Literature of the Beginning of XX Century on the Example of Płomyk. Z pamiętnika instytutki Novel by Eugenia Żmijewska - Kępa, Sylwia (Starość i młodość w literaturze i kulturze, 2016)
The aim of this paper is to present the character and mentality of adolescent girl from a family oflandowners, on the example of the heroine of a novel Płomyk. Z pamiętnika instytutki of 1907, originatingfrom the mainstream of so-called ‘trivial’ literature. This novel (in the form of a diary) could be regardedas an interesting example to follow, set in the second half of the 20th century patterns of realistic positivistprose. Eugenia Żmijewska, the author of that piece, on one hand, refers to the positivist model under thesign of Orzeszkowa and Sienkiewicz, on the other hand, Żmijewska deftly combines the aesthetics of thenovel with a plot of schoolgirl.The result of this syncretism is the character of Dola Żalińska. In the personality of that heroine— passing a difficult period of adolescence — interweare and collide patterns of landowner education,strict school education and dilemmas of adolescence. This paper will pose a question of pararrels betweenliterary portrait of young lady and cultural image of schoolgirl raised in the late 19th and early 20thcentury.